The Educational Attainment of the Children of the Danish ?Guest Worker? Immigrants - Vibeke Jakobsen; Nina Smith (Institute for the Study of Labor (IZA), 2003)
This paper analyses the educational attainment of young first generation immigrants in Denmark who are children of the ?guest workers? who immigrated from Turkey, Pakistan and Ex-Yugoslavia in the late 1960s and early 1970s. Beside the traditional intergenerational transmission mechanism, we analyse potential immigrant-specific factors as language proficiency, attending mother-tongue courses and expectations concerning out or return migration from Denmark. The results show that intergenerational transmission effects are strong among ?guest worker? immigrants, especially among men. Other important factors are Danish language proficiency, age at first marriage and a number variables reflecting parents? and own attitudes concerning education, marriage and family. However, the ?guest worker? immigrants are not a homogenous group. The analyses reveal large differences between Turkish, Pakistani and Ex-Yugoslavian ?guest workers? with respect to their educational success and the factors behind.
Keywords: J24; J61; 330; education; ?guest worker? immigrants; intergenerational transmission; Ausländische Arbeitskräfte; Kinder; Bildungsniveau; Migranten; Generationenbeziehungen; Haushaltsökonomik; Schätzung; Dänemark